Time domain analysis of non-Markovian stochastic Petri nets with PRI transitions. - Horvath, A.
The time domain analysis of non-Markovian stochastic Petri nets with pre-emptive repeat identical (PRI) type transitions is considered in this paper. The set of "time domain" equations describing the evolution of the marking process is provided. The relation of the time domain and formerly available transform domain description is discussed. Based on the time domain description of the process, a simple numerical procedure is provided to analyze the transient behavior. Two examples are calculated to illustrate the proposed numerical method.
Keywords: Differential equations; First order approximation; Marking process; NonMarkovian stochastic Petri nets; Preemptive repeat identical transitions; Queuing model; Time domain analysis; Transient behavior